A randomized, double-blind pilot study of analgesic and anti-inflammatory effects of naproxen sodium and acetaminophen following dental implant placement surgery - Theken, Katherine N.; Chen, Mengxiang; Wall, D. Lucas; Pham, Truongan; Secreto, Stacey A.; Yoo, Thomas H.; Rascon, Allison N.; Chang, Yu-Cheng; Korostoff, Jonathan M.; Mitchell, Claire H.; Hersh, Elliot V. (Frontiers in Pharmacology, 2023)
Post-surgical pain following dental implant placement surgery is typically managed with non-opioid analgesics, including non-steroidal anti-inflammatory drugs (NSAIDs) and acetaminophen. However, the comparative analgesic efficacy of over-the-counter doses of NSAIDs and acetaminophen in implant patients is unknown. Therefore, we compared the analgesic and anti-inflammatory effects of naproxen sodium and acetaminophen after surgical placement of one or two dental implants. Adult patients were treated with naproxen sodium (440 mg loading dose + 220 mg q8h, n=15) or acetaminophen (1000 mg q6h - max daily dose 3000 mg, n=15) for three days after implant placement in a randomized, double-blind design. Pain was assessed on a 0-10 scale every 20 minutes for 6h after study medication treatment. Tramadol (50 mg) was available as a rescue medication. Plasma and gingival crevicular fluid (GCF) were collected prior to the surgery and 0, 1, 2, 4, 6, 24, and 72h after surgery for quantification of interleukin (IL)-6, IL-8, and IL-1β levels. Pain scores were significantly lower in patients treated with naproxen sodium compared to those treated with acetaminophen. Inflammatory mediator levels in plasma and GCF increased after surgery and returned to near baseline levels by 72h. Plasma IL-6 levels were significantly lower 6h after surgery in patients treated with naproxen sodium compared to acetaminophen. No differences in inflammatory mediator concentrations in GCF were observed between the treatment groups. The number of implants placed and body mass index (BMI) influenced inflammatory mediator concentrations in plasma and GCF, respectively. Naproxen sodium was more effective than acetaminophen in reducing post-operative pain and systemic inflammation following surgical placement of one or two dental implants. Further studies are needed to determine whether these findings are applicable to more complex implant cases and how they affect clinical outcomes following implant placement. ClinicalTrials.gov: NCT04694300.